Combustion Characteristics Study Of Low Grade Producer Gas From Carbonized Empty Fruit Bunch (EFB) Briquettes Gasification - Singh, Suraj (Universiti Sains Malaysia, 2022)
Malaysia has been searching for affordable, renewable energy alternatives as a result of the global problem of the depletion of fossil fuels, and biomass briquettes are one of the best solutions for reducing this depletion. In Malaysia, Empty Fruit Bunch (EFB) is one of the most widely used agricultural wastes, and its briquettes have the potential to be used as a substitute gaseous fuel. EFB, however, has a number of undesirable qualities that limit its quality as a reliable fuel source, necessitating a pre-treatment process in order to convert it into biomass briquettes. In this final year project, the combustion characteristic of a low-grade producer gas from carbonized Empty Fruit Bunch (EFB) briquettes through gasification process will be studied. The pre-treatment conducted will be are drying process by 40- 50oC, carbonization process by 350oC and 4 hours, mixing process with tapioca binder with 100:110:20 ratio and briquetting process using manual briquette machine at 150MPa. Once the pre-treatment is conducted, briquette analyzation will be conducted. This will consist of proximate analysis, physical analysis, calorific values and burning rate test of a single EFB briquette. The EFB briquettes will be compared to Fire Starter briquettes and with reference data of various ratio of briquettes. The briquettes will then undergo gasification process with 5 kg/h feed rate at 480oC in 20 minutes for the entire process where the gas produce will be tested under the Gas Chromatography. Using the data given, calculation carbon conversion efficiency is done. This will determine whether the briquettes made can produce producer gas.